Solar cells : materials, manufacture and operation - Markvart, T.; Castaner, Luis (Elsevier Advanced Technology, 2005)
The capture and use of solar energy has been growing for many years, but only in recent times have advances in design and manufacture allowed us to see the incorporation of solar energy as a significant player in the renewable energy arena. Solar cells are at the heart of any photovoltaic system and in this book the various types are described and their characteristics reviewed. Going beyond materials, design and function, Solar Cells also covers their testing, monitoring and calibration thus providing a comprehensive account of current activity in this important field of research and industry. Solar Cells has been abstracted from the recent Practical Handbook of Photovoltaics by the same editors (ISBN 185617 3909. 2003: Elsevier) Internationally-respected contributors from industry and academia Abstracted from The Practical Handbook of Photovoltaics' by the same Editors A comprehensive source-book on all aspects of solar cells.